Critical Thinking in Zeiten der Unübersichtlichkeit: Grundzüge eines neuen Lehrveranstaltungskonzepts - Löffler, Winfried (Österreichisches Religionspädagogisches Forum, 2024)
Since the curriculum reform in 2021, a course in Critical Thinking has been part of the theological curricula at the University of Innsbruck; it is also frequently enrolled by students from outside the Faculty of Theology. Its introduction follows an existing Anglo-Saxon tradition on the one hand and goes back to experiences in logic teaching on the other. This article analyses the aims, the backgrounds in philosophical anthropology, the history of ideas and the academic and social relevance of Critical Thinking, and considers how it can be suitably implemented in the context of theological studies.